2014
DOI: 10.5640/insc.040101
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Benzodiazepines, Following Liquid Chromatography, for Applications in Pharmaceutical, Biomedical and Forensic Investigations

Abstract: Abstract:Benzodiazepines are an important class of drugs commonly administered with a potential for abuse and environmental pollution. This review focuses on the liquid chromatographic electrochemical detection of the benzodiazepine class of drugs. These are characterised by a readily electrochemically reducible azomethine group, with a number also substituted by other electrochemically active groups. Liquid chromatography employing both single and dual electrode detection has been reported for a variety of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
(46 reference statements)
0
8
0
2
Order By: Relevance
“…Indeed, other researchers reported sediment drug concentrations that were in the same range as reported in this work. [44][45][46] It is also important to note that 0.4 g of sediment was used in the present work. The amount of sediment could be increased and consequently, better LODs could be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, other researchers reported sediment drug concentrations that were in the same range as reported in this work. [44][45][46] It is also important to note that 0.4 g of sediment was used in the present work. The amount of sediment could be increased and consequently, better LODs could be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The subject is divided into two main areas, polarographic and voltammetric applications, including details of methodology, design, and performance of selected applications. Those utilising liquid chromatography with electrochemical detection have been reviewed recently [30]. Discussion is focused on research papers published in the past 12 years.…”
Section: Electrochemical Behaviour Of Benzodiazepinesmentioning
confidence: 99%
“…The LC ED determination of benzodiazepines has recently been review [68] and has been shown to be a highly sensitive and selective approach. A number of further investigations have been reported since this review in 2014.…”
Section: Benzodiazepinesmentioning
confidence: 99%